A Frequency Reconfigurable UWB Monopole Antenna with Slotted Ground Structure (International Journal of Engineering and Computer Science, 2017)
In this modern world, there has been a significant drive to increase the functional density of consumer devices, especially hand-held electronics. In order to meet this challenge all the components need to be miniaturized. Most commonly used component in modern electronics is an antenna. The size of an antenna is directly related to its operational frequency. Frequency tunable miniaturized antennas are required for next generation electronics. In the existing system a multi-layered metamaterial-inspired antenna with a pixel grid loading structure is explained. In order to produce desired performance appropriate pixel configuration need to be selected. Simulations show that the antenna can be tuned over a wide frequency range by appropriate choice of pixel states. Here we are proposing a novel compact frequency-reconfigurable monopole antenna with various switchable states. Using a switchable slotted structure on the ground plane, the antenna can achieve frequency configuration capability. The proposed antenna has a combined UWB and narrowband functionality, has a good potential for use in cognitive radio. The simulations are done using HFSS (High Frequency Structure Simulator) software.